Modal Kultural Perempuan Mandar sebagai Silent Bargain dalam Jalur Teripang: Suatu Perspektif Historis - Ruslin, Ismah Tita; Alamsyah, Anggriani; Utaminingsih, Nur (ILMU POLITIK UNIVERSITAS ISLAM NEGERI (UIN) ALAUDDIN MAKASSAR, 2025)
This study examines the authority of women in maritime culture through a historical analysis that underscores cultural dimensions as manifestations of gender. The historical pursuit of trepang (sea cucumbers) by seekers from the port of Makassar to Australia’s northern coast has continued from the 16th century to the early 20th century, commonly referred to as the trepang route. This study addresses women’s cultural capital, emphasising power dynamics that have been underrepresented in maritime cultural studies, particularly as shipping and commercial activities have predominantly been associated with male authority. This research employs Bourdieu’s concept of cultural capital to illustrate the expertise of Mandar women in weaving Karoroq (sail) for Padewakkang boats utilised in the trepang trade. The Karoroq sail plays a vital role in the Padewakkang voyage to Arnhem Land, Australia, where trepang were harvested. The Padewakkang vessel, which lacks an engine, is entirely propelled by its sails. This study not only highlights the technical involvement of women in preserving maritime cultural heritage but also explores how Mandar women have historically demonstrated their power through traditional knowledge and the reinforcement of cultural identity. Furthermore, this study illustrates the status of women as equals to men within the maritime culture of Sulawesi for several decades. The authors perceive women's efforts to leverage cultural capital in the trepang route as a silent negotiation.